Individualizacija podgotovki k Olimpijskim igram v sportivnoj gimnastike (na materiale finalov v mnogobor'e sredi muzhchin) - Verniaiev, O.; Omelianchik-Ziurkalova, O.; Saliamin, Y.; Dobrovolskii, E. (Science in Olympic Sport, 2018)
Objective. To identify the relationship between training loads and competitive performance under individualized training in artistic gymnastics for the Olympic Games. Methods: analysis of data from specialized scientific and methodological literature; analysis of the competition protocols of 8 finalists in gymnastic all-around competition of the international competitions: European Championships, the World Championship, the World Cups, the Olympics Games in the period from 2015 to 2016; statistical analysis methods. Results. The paper addresses individualization of training of highly qualified gymnasts within the macrocycle for the Rio de Janeiro Olympic Games. It was found that the training plan for highly qualified gymnasts can differ greatly from the standard plan. The principle of an individual approach to the distribution of training and competitive loads provided by the personal coach of Oleg Vernyayev was analyzed. We found that there are relationships between training volume, participation in additional control-simulation training sessions and competitive performance.The data of the protocols of men's gymnastic all-around competitions for the period from 2015 to 2016, which shows the performance of Oleg Vernyayev was studied. At the qualifying World Championship, the athlete finished in fourth with a score of 89.625 points, and 8 months later, at the Games of the XXXI Olympiad, Oleg Vernyayev won a silver medal with a score of 92.266. Conclusion. On the basis of the obtained data, it was established that individualization of Oleg Vernyayev training was planned taking into account the individual capabilities of the gymnast and with the appropriate timing of the final competitions.